Extension Of Time in Construction Industry - Tan, Ying Xuan (2013)
Delay is the most common activities in the construction industry and it might be because of some relevant events caused by the owner, consultants, contractor, subcontractors and etc. these delays not only will cause the construction works beyond the period of completion and they might cause the overall project beyond the budget. All of the parties have the ability to prevent the EOT happen in this project in order to reduce any loss and expense of the client or themselves as well. For example, if the delay is caused the contractor then he/she needs to take responsibilities for the L.D in other way, the contractor will be given the additional time to complete the defaults as as the remaining work if delay is not the contractor’s fault. The main purpose to produce this research is to understand the EOT, identify the specification of the EOT, the factor of EOT as well as the prevention of EOT. Besides, this research also carried questionnaire survey with the experience personnel and contract administrative in order to understand more about the cause of EOT and try to find the way to reduce the probability of EOT happen in the construction industry